The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/1078-0432.ccr-13-3271
|View full text |Cite
|
Sign up to set email alerts
|

Association of PD-1, PD-1 Ligands, and Other Features of the Tumor Immune Microenvironment with Response to Anti–PD-1 Therapy

Abstract: Purpose Immunomodulatory drugs differ in mechanism-of-action from directly cytotoxic cancer therapies. Identifying factors predicting clinical response could guide patient selection and therapeutic optimization. Experimental Design Patients (N=41) with melanoma, non-small cell lung carcinoma (NSCLC), renal cell carcinoma (RCC), colorectal carcinoma or castration-resistant prostate cancer were treated on an early phase trial of anti-PD-1 (nivolumab) at one institution and had evaluable pre-treatment tumor spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

56
1,753
6
19

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,069 publications
(1,874 citation statements)
references
References 44 publications
56
1,753
6
19
Order By: Relevance
“…The results from the present study, with immune cell-specific PD-L1 expression being an independent prognostic factor while its expression in tumour cells was not, are coherent with previous research 16 , 23-26 and demonstrate that PD-L1 expression in immune cells and tumour cells might carry different prognostic values and might be regulated by distinct mechanisms. Furthermore, although tumour cell-specific PD-L1 expression has been validated as a predictive marker for response to PD-1 or PD-L1 blockade in several cancers, 11 , 38 , 39 recent studies now suggest that PD-L1 expression in tumour-infiltrating myeloid and T cells also play a critical role in immunosuppression, 38 , 40-43 and should possibly be taken into account in assessment scoring for PD-1/PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the present study, with immune cell-specific PD-L1 expression being an independent prognostic factor while its expression in tumour cells was not, are coherent with previous research 16 , 23-26 and demonstrate that PD-L1 expression in immune cells and tumour cells might carry different prognostic values and might be regulated by distinct mechanisms. Furthermore, although tumour cell-specific PD-L1 expression has been validated as a predictive marker for response to PD-1 or PD-L1 blockade in several cancers, 11 , 38 , 39 recent studies now suggest that PD-L1 expression in tumour-infiltrating myeloid and T cells also play a critical role in immunosuppression, 38 , 40-43 and should possibly be taken into account in assessment scoring for PD-1/PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumour cell-specific expression of PD-L1 was significantly associated with immune cell-specific PD-1 and PD-Ll expression, supporting results from other studies. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Although the elements involved in tumor response are complex, 10 studies seeking biomarkers that might be used to predict response to anti-PD1 antibody have found that tumor expression of PD-L1 is the single feature most highly correlated with response. 49,50 It has been suggested that cancer patients who do not respond to treatment with anti-PD1 antibodies are those having tumors with relatively low expression of PD-L1. 2, 5052 Our experiments revealed that SGT-53 treatment up-regulated PD-L1 expression in cultured 4T1 cells and in mouse syngeneic breast tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The programmed death 1 (PD-1)/PD-ligand 1 (PD-L1) immune checkpoint is one of the mechanisms employed by cancer cells to evade T cell mediated endogenous antitumor responses [4][5][6][7]. Immunotherapy agents targeting the PD-1/PD-L1 pathway have achieved durable treatment effects in patients with various cancer types including EBV-associated malignancies [5,6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy agents targeting the PD-1/PD-L1 pathway have achieved durable treatment effects in patients with various cancer types including EBV-associated malignancies [5,6,[8][9][10]. Positive tumor PD-L1 expression by immunohistochemistry in pre-treatment specimens is thought to be predictive of clinical response [5,9].…”
Section: Introductionmentioning
confidence: 99%